Finance and Development, September 1984. (Finance and Development; Finance and Development ;, 1984)
This paper examines the impact of the World Bank on the financial markets and developing countries. The sound financial structure of the Bank rests on its conservative loan-to-capital ratio. Its large liquidity is an assurance to investors in Bank bonds that their investments are assured of liquidity in case the need arises. To cope with their payments difficulties, the heavily indebted developing countries have adopted more cautious fiscal and monetary policies, limited wage increases, and reduced domestic consumption and investment.